Influenza Infection in Mice Induces Accumulation of Lung Mast Cells through the Recruitment and Maturation of Mast Cell Progenitors - Zarnegar, Behdad; Mendez-Enriquez, Erika; Westin, Annika; Söderberg, Cecilia; Dahlin, Joakim S.; Grönvik, Kjell-Olov; Hallgren, Jenny (Frontiers in Immunology, 2017)
Mast cells are powerful immune cells that mature in the peripheral tissues from bone marrow-derived mast cell progenitors. Accumulation of mast cells in lung compartments where they are normally absent is thought to enhance symptoms in asthma. The enrichment of lung mast cells is also observed in mice subjected to models of allergic airway inflammation. However, whether other types of lung inflammation trigger increased numbers of mast cell progenitors, which give rise to mast cells, is unknown. Here, mouse-adapted H1N1 influenza A was used as a model of respiratory virus infection. Intranasal administration of the virus induced expression of VCAM-1 on the lung vascular endothelium and an extensive increase in integrin 7hi lung mast cell progenitors. Experiments were performed to distinguish whether the influenza-induced increase in the number of lung mast cell progenitors was triggered mainly by recruitment or in situ cell proliferation. A similar proportion of lung mast cell progenitors from influenza-infected and PBS control mice were found to be in a proliferative state. Furthermore, bone marrow chimeric mice were used in which the possibility of influenza-induced in situ cell proliferation of host mast cell progenitors was prevented. Influenza infection in the chimeric mice induced a similar number of lung mast cell progenitors as in normal mice. These experiments demonstrated that recruitment of mast cell progenitors to the lung is the major mechanism behind the influenza-induced increase in lung mast cell progenitors. Fifteen days post-infection, the influenza infection had elicited an immature mast cell population expressing intermediate levels of integrin 7, which was absent in controls. At the same time point, an increased number of toluidine blue+ mast cells were detected in the upper central airways. When the inflammation was resolved the mast cells that accumulated in the lung upon influenza infection were gradually lost. In summary, our study reveals that influenza infection induces a transient accumulation of lung mast cells through the recruitment and maturation of mast cell progenitors. We speculate that temporary augmented numbers of lung mast cells are a cause behind virus-induced exacerbations of mast cell-related lung diseases like asthma.